KESIAPAN CALON GURU MATEMATIKA DALAM MENGHADAPI TANTANGAN ABAD 21: PERSPEKTIF PEDAGOGIS DAN INOVASI PEMBELAJARAN - Safitri, Rizka Safitri; Suparni; Sintha Sih Dewanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores the pedagogical readiness and learning innovations of prospective mathematics teachers in addressing the challenges of 21st-century education. The rapid advancement of technology and digitalization requires education to incorporate 21st-century skills, including critical thinking, creativity, collaboration, and digital literacy, into the learning process. This study employs a descriptive qualitative approach, with the research participants consisting of 29 students from the Mathematics Education Program enrolled in the course